2005
DOI: 10.1177/107602960501100209
|View full text |Cite
|
Sign up to set email alerts
|

The Plasma Levels of Prostanoids and Plasminogen Activator Inhibitor-1 in Primary and Secondary Thrombocytosis

Abstract: An elevated platelet count is a common finding in both hospitalized and ambulatory patients. Thrombosis and bleeding complications are more frequently observed in patients with clonal thrombocytosis than secondary thrombocytosis. The aim of this study was to investigate the behaviors of plasminogen activator inhibitor type 1 (PAI-1), the inhibitor of fibrinolysis; and thromboxane A2 and 6-keto-PGF1 alpha, the products of endoperoxides, in 16 patients affected with clonal thrombocytemia as compared with 16 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Specifically, hypofibrinolysis is driven by elevated levels of plasminogen activator inhibitor-1 (PAI-1) and platelet factor 4 (PF4). These proteins are associated with excessive platelet reactivity, not with the platelet count, which is in line with our results confirming the relationship between lower platelet count and thrombosis risk (Pósán et al 1998 ; Birdane et al 2005 ; Malecki et al 2016 ). It should be stressed that activated platelets and leukocytes in ET patients were found to be the main source of tissue factor (TF) and that reduced activity of the TF pathway inhibitor additionally increases the prothrombotic risk in JAK2 V617F positive ET patients (Gadomska et al 2016 ).…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, hypofibrinolysis is driven by elevated levels of plasminogen activator inhibitor-1 (PAI-1) and platelet factor 4 (PF4). These proteins are associated with excessive platelet reactivity, not with the platelet count, which is in line with our results confirming the relationship between lower platelet count and thrombosis risk (Pósán et al 1998 ; Birdane et al 2005 ; Malecki et al 2016 ). It should be stressed that activated platelets and leukocytes in ET patients were found to be the main source of tissue factor (TF) and that reduced activity of the TF pathway inhibitor additionally increases the prothrombotic risk in JAK2 V617F positive ET patients (Gadomska et al 2016 ).…”
Section: Discussionsupporting
confidence: 93%
“…28 Nevertheless, the platelet contribution to PAI-1 plasma levels is controversial, because the majority of PAI-1 in platelets has been reported to be inactive compared with plasma PAI-1, which is mainly active. However, this observation could be due to preparation artifacts, and the majority of platelet PAI-1 may be active.…”
Section: Mechanisms Regulation and Sources Of Pai-1mentioning
confidence: 99%
“…About 90% of the total PAI-1 in blood derived from platelet α-granules and platelet count were correlated with plasma PAI-1 concentrations [ 80 ]. Recent findings showed that more than 50% of platelet PAI-1 is in the active configuration, contrary to preliminary studies where the majority of PAI-1 stored in platelets has been considered to be inactive [ 81 ].…”
Section: Molecular Connections Between Platelets and Components Of Pl...mentioning
confidence: 99%